Expert opinion: metformin in the prevention and treatment of weight gain during antipsychotic drug therapy - Murawiec, Sławomir (Psychiatria Spersonalizowana / Personalized Psychiatry, 2024)
The introduction of second-generation antipsychotics into psychiatric practice has been associated with significant advances in treatment options for schizophrenia and other disorders. However, the weight gain associated with the use of this group of drugs is a major limitation to their use and negatively affects patient compliance. As a result, methods have been sought to reduce the impact of this unfavorable factor. This paper reviews the scientific literature on the use of metformin as a method of early intervention (to limit weight gain) and as a method of treating weight gain that has already occurred during antipsychotic drug therapy. The use of metformin can lead to a weight loss of about 3 kg in those being treated and can prevent a weight gain of about 5 kg in those starting treatment.